Revealing the limitations of 10-year MACE observations: 20-year observed total cardiovascular burden in the EPIC-Norfolk study - Frank LJ Visseren; Harald T Jorstad; Marjolein Snaterse; S Matthijs Boekholdt; Tinka J van Trier; Jannick AN Dorresteijn; Manon van den Bogaart; Wilma JM Scholte op Reimer; Ron JG Peters (Open Heart)
Background Primary prevention strategies for cardiovascular disease (CVD) conventionally rely on 10-year risk estimates of major adverse cardiovascular events (MACE). However, communicating longer-term total CVD risk may better facilitate informed preventive decisions. Therefore, we aimed to quantify how well 10-year observed incidence reflects 20-year observed incidence and how MACE reflects total CVD events across demographic groups, using observations in long-term prospective data.Methods In individuals aged 40–79 without CVD or diabetes from the population-based EPIC-Norfolk cohort, we compared the first occurrence of 10 and 20 years (1) 3-point MACE events (non-fatal myocardial infarction+non-fatal stroke+fatal CVD) and (2) total CVD events (all non-fatal and fatal CVD events leading to hospitalisation), stratified by sex and age.Results Among 22 569 participants (57% women), incident 10-year and 20-year 3-point MACE was 5.3% and 15.5%, respectively, yielding 20/10 year ratios from 2.2 (in older men) to 4.5 (in younger women). Total CVD increased from 10.5% at 10 years to 26.9% at 20 years, with ratios ranging from 1.9 (older men) to 3.9 (younger women). Ratios between 10-year MACE and 20-year total CVD varied substantially, ranging from 3-fold in (older men) to 10-fold (younger women).Conclusions The observed incidence of CVD roughly triples from 10 to 20 years of follow-up, with 10-year MACE observations underestimating 20-year total CVD burden by a factor ranging from 3 (older men) to 10 (younger women). These findings highlight the limitations of communicating 10-year MACE risk assessments to facilitate informed decisions in longer-term CVD prevention—particularly in younger women.